Pengaruh Pemasaran Media Sosial, Word Of Mouth dan Kualitas Produk terhadap Kepuasan Konsumen Richeese Factory di Kota Solo - Adivarani Diaz Rahmawati; Eka Darma Ningtyas; Rayhan Gunaningrat; R. Taufiq Nur Muftiyanto (International Forum of Researchers and Lecturers, 2024)
The ever-growing global business world provides opportunities for the food industry, the large number of fast food restaurants in Indonesia causes intense competition in fighting for the quality and quality of the products produced. Researchers chose Richeese Factory as the research target because it is the only fast food restaurant that has superior product innovation, namely crispy fried chicken topped with spicy sauce and cheese sauce so that it can attract consumers' attention when consumers are more selective and innovative in choosing fast food restaurant products. A quantitative approach was taken in this study. A questionnaire created with Google Form media was used to collect data. 100 respondents made up the sample, which was selected through non-probability sampling methods. In this method, the population or elements selected as samples do not have the same chances or opportunities. The study's findings demonstrate that product quality has no bearing on customer satisfaction, word-of-mouth has a big impact on satisfaction, and social media has no effect at all.